Biotechnology method to improve nutritional quality in rice / Siti Noormaizurah Mohd Rashid and Nor Azma Yusuf - Mohd Rashid, Siti Noormaizurah; Yusuf, Nor Azma (Faculty of Plantation and Agrotechnology, 2018)
Rice feeds more than two billion people worldwide and is the number one staple food in Asia. It provides 40-70% of the total daily food calories consumed, however, is low in bio available micronutrients required for the daily diet. Major staple crops especially rice is often deficient in some of the nutrients required in human diet. Thus, malnutrition is a major problem, especially in developing countries, where a diversified diet is not affordable for the majority. Furthermore, today's global population of six billion people is expected to reach eight billion by 2020. Therefore, the production of rice must be increase to 25-40% more rice with less land and water and with a reduced use of agrochemicals. Basically, this study is to review biotechnological method to improve nutritional quality in rice. In addition, slight development in improving the nutritional quality in rice can give a dramatic impact on human health. However, nutritional enhancement of crops through conventional breeding is often limited by the low genetic variability for required dietary micronutrients level. Thus, biotechnology methods such as genetic modification and modem breeding techniques holds promising possibilities for food-based solutions to overcome malnutrition deficiencies. Based on this review there are four biotechnology applications that can be done to improve nutritional quality in rice including increasing iron (Fe) content, increasing vitamin A, increasing lysine and decreasing anti nutrients content. It is true that biotechnology method can help in improving nutritional quality in rice and the nutritional composition in rice is importance to human health.